Promosi: Pemanfaatan Media Sosial dan E-Wom Communication pada Minat Menjadi Mahasiswa (Survei pada Followers akun Facebook UT Pangkalpinang) - Yusuf Yusuf (Journal on Education, 2024)
The aim of the research is to find out the description of promotion through social media and e-WOM Communication and the interest in becoming a student among UT Pangkalpinang Facebook followers, and its partial and simultaneous influence so that information can be obtained to increase the best promotion in increasing interest in becoming a UT Pangkalpinang student. The research methodology used is a quantitative descriptive statistical approach. The sample consisted of 257 students with a population of 4,958. This type of data uses primary data by distributing digital questionnaires. Data analysis techniques use descriptive tests and multiple linear regression analysis. The research results show: [1] all dimensions have a high average value (3.41-4.20). [2] partially there are 7 dimensions that have a significant effect and 2 dimensions that have no significant effect. The dimensions that have a significant influence are context, communication, connection (variable promotion via social media), platform assistance, concern for others, social benefits and helping the company (variable promotion via e-WOM Communication). Meanwhile, the variables that do not have a significant effect are collaboration (variable promotion via social media) and positive self-enhancement (variable promotion via e-commerce communication) [3] Simultaneously, all dimensions have a significant influence on student decision making (296,384>19,492). This means that every time there is an increase or decrease in the dimensions and independent variables together, they will have a significant influence on the interest in becoming a student among UT Pangkalpinang Facebook followers.